University Oriental College Lahore in Light of History and Culture - Imran Ali; Muhammad Ijaz Tabassum (بازیافت)
<span style="font-size: 14.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Oriental College is first educational institution of Governemnt of Punjab, where Oriental Languages are taught. Oriental College was established in 1870, basically this Institution was established to acquaint the people with modern field of knowledge in Oriental Languages. At that time Arabic, Persian, Sanskrit, Hindi, Urdu, Punjabi (Grumukhi) and Peshto, including modern subjects of knowledge, like Engineering, Mathematic, Geography, Economic, Philosophy, Muslim Law, Dharam Shaster, Medicine, Economic, Tibb Unani, Vedak and History were taught in this College. <span style="font-size: 14.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">M.A. classes were started at Oriental College beginning with Arabic, M.A. Sanskrit 1888, Persian 1921, Urdu 1948, Punjabi 1970 and Kashmir Studies 1987.